FEATURES SYMPTOMS OF DOMESTIC CATS PARAANAL ADENITUM IN TERMS OF THE VETERINARY CENTRE «RED CAT» - Палій, Л. М. (Scientific Progress & Innovations, 2014)
The article presents the results of clinical evaluation of cats with the aim of paraanal adenitum diagnosing. The cats came to outpatient admission to veterinary centre «Red cat». Clarified sex, breed, age-related predisposition to this disease. On the basis of the collected anamnesis and clinical examination and functional diagnostics defined pathological changes that accompany this disease. In particular we defined the tensile glands, inflammation, narrowing of the excretory ducts, change of the inflammatory exudate color.